Avaliação do esvaziamento gástrico de pacientes com gastroparesia utilizando a cintilografia - Viviana Montoya Ojeda (2018)
Gastric emptying \(GE) is an important function of the stomach that impacts on patients' quality of life. Alteration in this function is a reflection of some form of disorder in the gastrointestinal tract that can be affected by numerous diseases, such as gastroparesis. This is a disorder characterized by symptoms and evidence of delayed gastric emptying in the absence of mechanical obstruction. Several techniques have been evaluated to determine the time of gastric emptying, one of them is scintigraphy, a method considered "gold standard". Often, this technique is not ideal for patients with physical mobility problems, pregnant women, for whom the 13C-octanoic acid respiratory test (RT) becomes a promising alternative to scintigraphy, with the advantage of not using ionizing radiation. The two methods quantify the physiological emptying through the radiolabeled meal. The objective of this study was to evaluate the gastric emptying by means of the respiratory test and scintigraphy using two different test meals. Thirty patients were selected, being 26.7% male and 73.3% female. The patients' age ranged from 23 to 76 years, with a weighted average of 56.7 ± 13.4 years. The proposed diet with a more caloric content (319 kcal) and a more caloric diet was used simultaneously for the scintigraphy and RT. In the study, the retention percentage of radiolabelled food in the stomach was determined at 1, 2 and 4 hours after ingestion; the severity rating of the gastric emptying delay based on the retention value after 4 hours and the mean time (T½) of GE. The results obtained show that, for the time of 1 and 2 hours, the comparison of the two diets showed a significant difference (p = 0.02 and p = 0.001, respectively) and for the time of 4 hours, no (p = 0.1). With the standard diet, there were more patients with accelerated GE (10%) than the proposed diet (3.3%). In the proposed diet, there were more patients with severe delay (23.4%) than in the standard diet (10%). The agreement between the scintigraphy and the respiratory test was considerable (Kappa index of 0.377)